KAJIAN SIFAT KIMIA TANAH PADA LAHAN TERDAMPAK ABU VULKANIK GUNUNG SINABUNG - Nani Kitti Sihaloho (Universitas Quality, 2021)
The eruption of Mount Sinabung from 2010 to 2019 greatly damaged crops and agricultural land in the area, with damage varying from mild to very heavy, mostly due to land and crops being swept away by hot clouds and covered in lava and volcanic ash. One of the areas affected by the eruption of Mount Sinabung was Tigapancur Village, Simpang Empat District, but it was still classified as a safe zone so that agriculture is still active. The eruption of Mount Sinabung was very disturbing to agriculture, due to volcanic ash so that production has decreased. This study aims to assess the chemical properties of soil in areas affected by volcanic ash of Mount Sinabung in the Tigapancur Village, Simpang Empat District, Karo Regency and soil analysis at the Research and Development Laboratory of PT. Nusa Pusaka Kencana Analytical & Qc. The Tebing Tinggi Bahilang Laboratory of Medan from October to November 2019. The results showed that there were differences in soil chemical properties including the degree of acidity (pH) and unequal macro-essential elements (N, P, K, Ca, Mg, S), so they were divided into several criteria (very low, low, medium and very high) both on land not affected by volcanic ash with a depth range of 0 - 5 cm and 5 - 20 cm.